EFEKTIVITAS PENGGUNAAN MEDIA ONLINE TIRTO.ID TERHADAP PEMENUHAN KEBUTUHAN INFORMASI BERITA LIVI ZHENG (Survei Terhadap Mahasiswa Ilmu Komunikasi UPNVJ) - Mesi Indriyani, (2020)
Background in this research explains the use of Tirto.id media in meeting Livi Zheng news information needs. Online media is a place to get news information. The purpose of this study is to learn how to use Tirto.id online media in meeting the information needs of Livi Zheng news. The theory used in this study is the Theory of Use and Gratification, which is the theory of active audiences using media in an effort to meet their needs, both the technical needs of social communication. The research methodology used is quantitative, type of explanative research and survey methods and questionnaires. The population of this research is UPN "Veteran" communication science students in Jakarta. The sample of this study was 89 respondents using proportional stratified random sampling technique. The results of trials in this study indicate a moderate or strong enough relationship of 0.451. The coefficient of determination test results states that there is no significant effect of using media by 20.3% on the fulfillment of information needs. Hypothesis test results found t arithmetic 4.715> t table 1.662. The conclusion of this study is the insignificant relationship between the use of Tirto.id online media and the fulfillment of Livi Zheng's news information needs.